LOKAKARYA LITERASI DIGITAL DAN E-COMMERCE PELAKU USAHA MIKRO, KECIL, DAN MENENGAH DI DESA MAJAU - Nusantari, Farida Ayu Avisena; Mariani, Desy; Suryani, Suryani (Artinara, 2025)
MSME players in the current digital era are required to be able to adopt technology for business development so that they can reach a wider market, both national and international. The importance of digital literacy and the use of digital platforms such as e-commerce to increase competitiveness and operational efficiency has not been widely realized, especially among MSMEs in the regions. The aim of implementing this community service is to provide education to comprehensively increase understanding regarding digital literacy and e-commerce as well as provide ongoing assistance to Majau village, Pandeglang city. The method of implementing activities combines participatory and collaborative training methods which prioritize the application of participatory principles, namely the principle of role and involvement of participants to achieve training objectives with a total of 15 MSME players from various business fields. The result of this activity is that the MSME players involved showed significant improvements regarding digital understanding and marketing optimization by motivating digital transformation.